IDENTIFIKASI KEPRIBADIAN IDEAL KONSELING BERDASARKAN BUDAYA PESANTREN - Hafifuddin Nur; Abd. Mughni; Wawan Juandi (Fakultas Dakwah Universitas Ibrahimy, 2023)
Counselees are individuals who are the main subject in the guidance and counseling program that must be served and prospered. In pesantren culture, the counselee is a santri who has an obligation to study. In order for the knowledge gained to be useful and bring blessings, it is necessary to understand adab in seeking knowledge. One of the books that teaches about adab seeking knowledge that can be used as a reference for students is the book Adab Al-Alim Wal Muta’allim. This study aims to identify the counselee’s ideal personality based on the book of Adab Al-Alim Wal Muta’allim. The research method used is a qualitative approach of the Gadamerian Hermeneutics type which aims to interpret and understand the text in the book Adab Al-Alim Wal Muta’allim. The results of the study found ten ideal counselee personalities that were categorized as personal and interpersonal ideals, personal personality includes the counselee’s ideal personality that relates to himself personally while interpersonal personality includes the counselee’s ideal personality that relates to other people (counselors). The counselee’s ideal personality personally includes: Purifying oneself, Intention to seek the blessing of Allah, Trying as quickly as possible to gain knowledge, Qana’ah, Taking care of oneself, while the counselee’s personal ideal interpersonally includes: Right in choosing a teacher, Obedient, Respect, Patience, Politeness.